D-110 Synergism between CRISPR/Cas9 and LASER ART leads to elimination of HIV-1 with no rebound in Humanized Mice. (April 2018) - Gendelman, Howard; Dash, Prasanta; Edagwa, Benson; Gorantla, Santhi; Kaminski, Ratal; Bella, Ramona; Young, Won-Bin; Khalili, Kamel
Abstract : Treatment with long acting slow effective release (LASER ART) rilpivirine, myristolyated dolutegravir, lamivudine and abacavir followed by CRISPR-Cas9 proviral DNA excision led to viral eradication in HIV-1 infected humanized mice. Ultrasensitive nested and digital droplet PCR and RNA scope assays failed to detect HIV-1 in blood, spleen, lung, kidney, liver, gut-associated lymphoid tissue and brain in twenty-nine percent of infected animals treated with the dual regimen. Excision of proviral DNA fragments spanning the LTRs and the Gag gene were identified without identifiable off target effects. The absence of viral rebound following cessation of ART with no progeny virus recovery served to verify HIV-1 eradication. In contrast, HIV-1 was readily detected in all infected animals treated with LASER ART or CRISPR-Cas9 alone. Thus, sequential application of LASER ART and CRISPR-Cas9 therapies administered to HIV-1 infected humanized mice provides the proof of concept that viral sterilization is possible.